Basin Focal Project Volta - Lemoalle, J. (CGIAR Challenge Program on Water and Food, 2009)
The Basin Focal Project Volta (BFP Volta) was developed along three main steps: Assessment of present conditions of the distribution of rural poverty, of farming systems with their productivity and water productivity; Analysis of opportunities and risks, especially under the double pressure of demography and possible climate change, and modeling of water resources to identify sensitivity of water allocation to development and climate scenarios; and Identification of research gaps and implementation plan. The study indicated that while many technical solutions are available and identified, their socio-economic acceptability and implementation still need further research and efforts.